Bandgap Engineering and Oxygen Vacancies of NixV2O5+x (x = 1, 2, 3) for Efficient Visible Light‐Driven CO2 to CO with Nearly 100% Selectivity. Issue 7 (10th April 2022) - Chen, Yong; Zhang, Yuanming; Wang, Wenjing; Xu, Xiaoming; Li, Yang; Du, Mengyang; Li, Zhaosheng; Zou, Zhigang
Abstract : It is difficult to design a new single‐component photocatalyst to simultaneously possess a bandgap small enough to absorb most of sunlight and strong redox ability to reduce CO2 into value‐added chemical fuels. Herein, bandgap engineering of nickel vanadate compounds (Ni x V2 O5+ x, x  = 1, 2, 3) is rationally designed to overcome the above challenge. Through changing the Ni:V ratio, the bandgap and band edge positions of nickel vanadates can be regulated, enabling Ni2 V2 O7 and Ni3 V2 O8 to reduce CO2 in the presence of water under visible light irradiation that do not exist in NiV2 O6 . Ni 3 d orbitals of Ni2 V2 O7 and Ni3 V2 O8 replace V 3 d orbitals of NiV2 O6 and hybridize with O 2 p orbitals to form the valence band maximums, resulting in their negative shifts. Meanwhile, the relatively weaker effect of the crystal field in VO4 tetrahedron over Ni2 V2 O7 and Ni3 V2 O8 results in less V 3 d split, thus making the conduction band edges to shift upward. In addition, higher concentration of oxygen vacancies over Ni2 V2 O7 can further enhance its photocatalytic activity for CO2 conversion into CO with nearly 100% selectivity by prolonging the lifetime of photogenerated carriers and improving the chemisorption of CO2 . Abstract : Through changing the Ni:V ratio, the band gap and band edge of nickel vanadates could be regulated, enabling Ni2 V2 O7 and Ni3 V2 O8 samples to photocatalytic CO2 to CO in the presence of water under visible‐light irradiation, while NiV2 O6 sample showed almost no activity. Meanwhile, the higher concentration of oxygen vacancies over Ni2 V2 O7 sample further enhanced the photocatalytic activity for CO2 conversion into CO.